Pemberdayaan Masyarakat Melalu Pelatihan Pembuatan Sabun Cuci Piring Di Desa Pulau Sembilan Kecamatan Pangkalan Susu Kabupaten Langkat - Muhammad Irfan; Sarah; Ajeng Najihah; Indri Cantika; Dila Rohmayana; Maulida Husna Dalimunthe; Nur Acnes; Titah Maulana; Muhammad Yusuf Haldi (peduli riset dan pengabdian masyarakat, 2023)
The STAI Jam'iyah Mahmudiyah Community Service Program (KKN) team is interested in empowering the community by holding communication and telesoap production training and supporting their knowledge to help village communities by creating an activity called Community Empowerment. Through dishwashing soap conducting training in the village. We hope that the community can reduce the unemployment rate and increase the economic level by helping the community reduce the cost of purchasing dishwashing detergent and opening MSME business opportunities to the community with the emergence of Micro, Small and Medium Enterprises (MSMEs). The implementation of the KKN program takes place in three stages, namely: the preparation stage, the implementation or organization stage and the final stage. The result of this activity is that housewives can be creative in making a product, one of which is dishwashing soap, which sells quickly and can be sold, which can improve the family's economy. This activity was considered very useful, because the residents of Pulau Sembilan Village were very enthusiastic about participating in the training, so many housewives there wanted to try a washing machine to meet their daily needs.